2019
DOI: 10.3389/fpls.2019.01383
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of Rice—Magnaporthe oryzae Interaction: What Have We Learned So Far?

Abstract: Rice blast disease, caused by Magnaporthe oryzae, is one of the major constraints to rice production, which feeds half of the world’s population. Proteomic technologies have been used as effective tools in plant−pathogen interactions to study the biological pathways involved in pathogen infection, plant response, and disease progression. Advancements in mass spectrometry (MS) and apoplastic and plasma membrane protein isolation methods facilitated the identification and quantification of subcellular proteomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 114 publications
0
31
0
Order By: Relevance
“…Of these, ethylene has been most actively involved in PCD and is alone sufficient to cause PCD in many plant systems [130]. PCD is a vital process during growth and development, especially in the organization and maintenance of plants, and plays a crucial role in the several defense responses against certain types of environmental stresses, both abiotic including salinity stress [131,132] and biotic ones [133][134][135][136][137]. ROS accumulation is an important inducer of PCD in plant cells under stress conditions as ROS molecules such as H 2 O 2 and superoxide radicals (O 2 − ) can damage the cellular components [138].…”
Section: Modulation Of Plant Cell Death Under Salinity Stressmentioning
confidence: 99%
“…Of these, ethylene has been most actively involved in PCD and is alone sufficient to cause PCD in many plant systems [130]. PCD is a vital process during growth and development, especially in the organization and maintenance of plants, and plays a crucial role in the several defense responses against certain types of environmental stresses, both abiotic including salinity stress [131,132] and biotic ones [133][134][135][136][137]. ROS accumulation is an important inducer of PCD in plant cells under stress conditions as ROS molecules such as H 2 O 2 and superoxide radicals (O 2 − ) can damage the cellular components [138].…”
Section: Modulation Of Plant Cell Death Under Salinity Stressmentioning
confidence: 99%
“…Magnaporthe oryzae, the causal agent of rice blast disease, has caused huge losses in rice (Dean et al 2012). Recently, proteomics and metabolomics studies investigating rice response to M. oryzae infection were reviewed (Meng et al 2019;Azizi et al 2019). In addition to the influence of M. oryzae on the basic biological processes of the host, such as photosynthesis and primary metabolism, global studies over the past decade have elucidated the detailed interaction between rice and M. oryzae considering whole proteins and metabolites (for review, see Azizi et al 2019;Meng et al 2019).…”
Section: Response Of Rice To Fungimentioning
confidence: 99%
“…Proteins and metabolites, the final genome products, are involved in fundamental life processes. To overcome biotic stress, plants utilize multiple classes of proteins, including: (1) catalytic enzymes involved in cell wall modifications, phytohormones, ROS, and pathogenesisrelated (PR) proteins; (2) TFs and post-translational factors; and (3) receptors and receptor-like kinases (Wu et al 2016;Wu et al 2017;Meng et al 2019). Meanwhile, plant metabolites have distinct functions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their routine functions as molecular chaperons, PDI proteins have also been shown to regulate the PCD in plants [39]. PCD is the self-destruction of the infected cells and is one of the ways to check the transfer and multiplication of the invading pathogens [40]. It was shown that one PDI5 in Arabidopsis is involved in the regulation of PCD by physically interacting with the cysteine proteases [41].…”
Section: Fine-tuning Of the Redox Status Of The Cellsmentioning
confidence: 99%